Violencia contra la mujer en el distrito de Santiago de Surco - Universidad Ricardo Palma. Vicerrectorado de Investigación (2017)
Violence against women is a public health problem in our country, which has been underestimated to this day. More than half of the women in Peru have been victims of some type of violence; violence has been present in most of the moments of our lives, manifesting itself in various aspects either at the private level, as it is in the family, or publicly, whether at work, on the street or at the time of to formulate public policies. This is because, in our country, the idea that violence is the only method to submit and exercise control over the life of women still persists in our country, and it is a reality that demands firm responses from the State, society and justice operators in order to safeguard the integrity and dignity of women victims. This Research Report is one of the fundamental tools to achieve these purposes, because it is through this one that provides a broad panorama of the problem in the district of Santiago de Surco and the need to eradicate the violence that affects especially young and adult women, establishing strategic objectives, monitoring, evaluation, monitoring and implementation of workshops that contribute to the development of the same.